Performance and power. - Alexander, Jeffrey C. (Polity, 2011)
Performativity has emerged as a critical new idea across the humanities and social sciences, from literary and cultural studies to the study of gender and the philosophy of action. In this volume, Jeffrey Alexander demonstrates how performance can reorient our study of politics and society.